A comparative analysis of social vulnerability and proximity to coal‐fired power plants and windmill farms. Issue 3 (13th September 2021) - Crowley, Julia
Abstract: This research examines if there are differences in the social vulnerability of U.S. residents living within a five‐mile radius of a coal‐fired power plant compared to residents living within a five‐mile radius of a windmill farm ( N  = 5776) for facilities in operation as of April 2020. Two logistic regression models were created with demographic data for 2020 and 2010 to account for the decline of the coal power industry and rise of the wind power industry. Results suggest that U.S. census tracts with higher percentages of populations aged 25 and over with a Bachelor's degree, living in poverty, minorities, and employed in the utilities sector were significantly more likely to live within a five‐mile radius of a coal power facility than a wind power facility for both the 2020 and 2010 models. The only major discrepancy between the two models involved the percentage of owner‐occupied housing as the variable was only a significant predictor for the 2010 model. Census tracts with higher percentages of owner‐occupied housing were less likely to be located near a coal power facility. zh摘要: 本研究分析了2020年4月以前居住在分别以燃煤发电厂和风能发电厂为中心，半径为五英里范围内的美国居民（N = 5, 776）的社会脆弱性是否存在差异。使用2010年和2020年的人口统计数据提出了两个逻辑回归模型，用于解释煤电产业的衰退和风电产业的兴起。2010和2020模型分析结果都暗示，在持有学士学位的25岁及以上人口占比更多、生活更贫困、少数群体更多、以及更多在公用事业就职的美国人口普查片区中，居民更有可能居住在以煤电设施为中心，半径为五英里的范围内。两个模型唯一的重要差距与自有住房率相关，因为该变量仅在2010模型中是显著预测物。自有住房率更高的人口普查片区不太可能位于煤电设施附近。 Resumen: Esta investigación examina si existen diferencias en la vulnerabilidad social de los residentes de EE. UU. Que viven dentro de un radio de cinco millas de una central eléctrica de carbón en comparación con los residentes que viven dentro de un radio de cinco millas de una granja de molinos de viento (N = 5.776) para las instalaciones. en funcionamiento a partir de abril de 2020. Se crearon dos modelos de regresión logística con datos demográficos para 2020 y 2010 para dar cuenta del declive de la industria de la energía del carbón y el auge de la industria de la energía eólica. Los resultados sugieren que los distritos censales de EE. UU. Con porcentajes más altos de población de 25 años o más con una licenciatura, que viven en la pobreza, son minorías y están empleados en el sector de servicios públicos tenían una probabilidad significativamente mayor de vivir dentro de un radio de cinco millas de una instalación de energía de carbón que una instalación de energía eólica para los modelos 2020 y 2010. La única discrepancia importante entre los dos modelos involucró el porcentaje de viviendas ocupadas por el propietario, ya que la variable fue solo un predictor significativo para el modelo de 2010. Las secciones censales con porcentajes más altos de viviendas ocupadas por sus propietarios tenían menos probabilidades de estar ubicadas cerca de una instalación de energía de carbón.